2022
DOI: 10.1021/acs.cgd.2c00716
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of PbTiO3 Single Crystals with Flux and Laser Floating Zone Method

Abstract: PbTiO 3 is an established high temperature ferroelectric and component of multiferroic devices. Single crystal growth of clean PbTiO 3 has largely been limited to flux growth, in part due to the volatility of PbTiO 3 near the melting point. We demonstrate the ability to grow single crystals of PbTiO 3 using the laser diode floating zone technique. Crystal quality is examined using Laue, powder, and single crystal X-ray diffraction. Low temperature specific heat and annealing experiments using thermogravimetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Althou diffraction pattern of our crystals shows the typical lattice parameter [40] and and Raman measurements a correct sequence of the phase transitions [41,42, chemical point of view, the composition of the crystal due to the method shows a surplus of Pb. Most scientific articles dedicated to FE properties or d istry are based on such prepared crystals [44,[59][60][61][62][63], although some refineme able [64]. Using the chemical analysis ICP-OES (for determination of the con and Pb) and infrared spectroscopy (for the analysis of the amount of oxygen), that the chemical formula of our crystal can be written as follows: Pb1.02±0.02Ti This additional incorporation of a few percent of Pb in the matrix of the cr explained in two ways: either additional PbO will create a stacking fault in (PbO)0.06PbTiO3 [65][66][67][68], where an equidistant distribution of PbO planes wil RP phase [40]; or, if the valence of Pb is reduced to 4+, an anti-structural dis…”
Section: Surface Layer Xps Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Althou diffraction pattern of our crystals shows the typical lattice parameter [40] and and Raman measurements a correct sequence of the phase transitions [41,42, chemical point of view, the composition of the crystal due to the method shows a surplus of Pb. Most scientific articles dedicated to FE properties or d istry are based on such prepared crystals [44,[59][60][61][62][63], although some refineme able [64]. Using the chemical analysis ICP-OES (for determination of the con and Pb) and infrared spectroscopy (for the analysis of the amount of oxygen), that the chemical formula of our crystal can be written as follows: Pb1.02±0.02Ti This additional incorporation of a few percent of Pb in the matrix of the cr explained in two ways: either additional PbO will create a stacking fault in (PbO)0.06PbTiO3 [65][66][67][68], where an equidistant distribution of PbO planes wil RP phase [40]; or, if the valence of Pb is reduced to 4+, an anti-structural dis…”
Section: Surface Layer Xps Studiesmentioning
confidence: 99%
“…Although the X-ray diffraction pattern of our crystals shows the typical lattice parameter [40] and the dielectric and Raman measurements a correct sequence of the phase transitions [41,42,58], from the chemical point of view, the composition of the crystal due to the method flux growth shows a surplus of Pb. Most scientific articles dedicated to FE properties or defect chemistry are based on such prepared crystals [44,[59][60][61][62][63], although some refinements are available [64]. Using the chemical analysis ICP-OES (for determination of the concentration Ti and Pb) and infrared spectroscopy (for the analysis of the amount of oxygen), it was found that the chemical formula of our crystal can be written as follows: Pb 1.02±0.02 Ti 0.96±0.012 O 3±0.04 .…”
Section: Surface Layer Xps Studiesmentioning
confidence: 99%
“…Since the successful growth of silicon in the middle of the last century [27,28], the floating-zone technique has been widely applied to various categories of materials: oxides [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], chalcogenides [46][47][48][49], silicides [50][51][52][53][54][55], borides [56][57][58][59][60][61][62][63], carbides [64][65][66][67][68][69][70], and intermetallic alloys [71][72][73][74][75][76]…”
Section: Introductionmentioning
confidence: 99%
“…20−26 The technique thus presents a unique opportunity to improve upon the availability/properties of crystalline samples. 27 Here, we report the growth of single crystals of Bi 2 WO 6 using a laser diode floating zone technique. As grown crystals show the presence of oxygen deficiencies leading to the formation of W 5+ defect sites, providing an opportunity for post growth annealing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Such oxygen deficiencies result in W 5+ centers surrounded by oxygen octahedra. These centers in perovskite structures have been investigated for applications ranging from quantum information to electrochromic materials. Bulk crystal growth has been largely limited to flux methods due to the high-temperature phase transition that results in cracking upon cooling. The utilization of laser diode heating for floating zone furnaces (LDFZ) has enabled/improved the crystal growth of various systems, including those exhibiting high-temperature structural transitions. The technique thus presents a unique opportunity to improve upon the availability/properties of crystalline samples …”
Section: Introductionmentioning
confidence: 99%